Realization on the interactive remote video conference system based on multi-Agent - Zheng Yan; Li Wen Ting; Zeng Li; Ge Yu; Cai Xiao Yan; Meng Xian Yu (MATEC Web of Conferences, 2016)
To make people at different places participate in the same conference, speak and discuss freely, the interactive remote video conferencing system is designed and realized based on multi-Agent collaboration. FEC (forward error correction) and tree P2P technology are firstly used to build a live conference structure to transfer audio and video data; then the branch conference port can participate to speak and discuss through the application of becoming a interactive focus; the introduction of multi-Agent collaboration technology improve the system robustness. The experiments showed that, under normal network conditions, the system can support 350 branch conference node simultaneously to make live broadcasting. The audio and video quality is smooth. It can carry out large-scale remote video conference.